2020
DOI: 10.1108/jfra-10-2019-0137
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with IFRS 15 mandatory disclosures: an exploratory study in telecom and construction sectors

Abstract: Purpose The purpose of this study is to explore the degree of compliance of a sample of European Union (EU) listed groups with the International Financial Reporting Standard 15 (IFRS 15) mandatory disclosures in two specific sectors, namely, telecommunication and construction. Design/methodology/approach To carry out this research, the authors selected 22 annual reports for the year 2018. The authors created and completed a datasheet based on a close review of the IFRS 15 disclosure requirements. A content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…This suggested that in the company's opinion, a recheck of its long-term contracts and associated variable considerations did not significantly affect its financial position and performance. This position is corroborated by the works of Boujelben and Kobbi-Fakhfakh [48], Standler and Nadier [4] who found that while adopting the standard by entities led to an increase in levels of disclosures, minimal impact on the accounting numbers was reported. However, this view is not consistent with the studies of Trabelsi [29] and Aladwan [37] who posit that IFRS 15 post-implementation reviews of construction and related industries have a positive and significant effect on financial reporting quality and corporate performance.…”
Section: Dangote Cement Plcmentioning
confidence: 71%
“…This suggested that in the company's opinion, a recheck of its long-term contracts and associated variable considerations did not significantly affect its financial position and performance. This position is corroborated by the works of Boujelben and Kobbi-Fakhfakh [48], Standler and Nadier [4] who found that while adopting the standard by entities led to an increase in levels of disclosures, minimal impact on the accounting numbers was reported. However, this view is not consistent with the studies of Trabelsi [29] and Aladwan [37] who posit that IFRS 15 post-implementation reviews of construction and related industries have a positive and significant effect on financial reporting quality and corporate performance.…”
Section: Dangote Cement Plcmentioning
confidence: 71%
“…The present study adopted document analysis method. Document analysis method requires researchers to examine and interpret the data collected to extract the meaning, obtain understanding as well as develop empirical knowledge (Corbin and Strauss, 2008; Boujelben and Boujelben, 2020; Boujelben and Kobbi-Fakhfakh, 2020; Tadros et al , 2020; Evan et al , 2021). O’Leary (2014) has stated three main types of documents for document analysis which are public records, personal documents and physical evidence (Abdi et al , 2018; Weber, 2018; Al-Sartawi and Reyad, 2019; Abdi and Omri, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…A content analysis of the e-procurement website was carried out to assess the level of transparency of the e-procurement system. Prior studies have adopted content analysis on official documents (Weber, 2018; Nistor et al , 2019; Boujelben and Kobbi-Fakhfakh, 2020; Boujelben and Boujelben, 2020; Tadros et al , 2020); interviews (Evans et al , 2021); as well as websites (Abdi et al , 2018; Al-Sartawi and Reyad, 2019; Abdi and Omri, 2020). According to Krippendorff (2004), content analysis is a scientific technique that should result in replicability from the contexts used by the researcher.…”
Section: Methodsmentioning
confidence: 99%